High-heat-insulation and high-environmental-protection rare gold targeted heat-insulation film and production method thereof
Through the principle of electrostatic adsorption and magnetron sputtering deposition technology, a high-insulating, high-environmentally friendly dilute targeted thermal insulation film was prepared, solving the problems of residues and environmental pollution during the pasting and disassembly of existing thermal insulation films, and achieving high infrared barrier rate and high thermal insulation performance.
Patent Information
- Application Number
- CN202411882217.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing thermal insulation film requires glue or other adhesives during the pasting and disassembly, resulting in residues and environmental pollution and does not conform to environmental protection concepts.
Highly insulated, highly environmentally friendly, rare gold targeted insulation films are prepared using the principle of electrostatic adsorption. The insulation layer is deposited on both sides of the polyester film through magnetron sputtering deposition technology, and the star nanostructured lanthanum oxide and yttrium oxide rare earth nanoparticles absorb infrared and ultraviolet rays.
The thermal insulation film can be pasted and disassembled without glue, avoiding residues and environmental pollution, and has high infrared barrier rate and high thermal insulation, suitable for curtain wall glass and automotive window glass.
Smart Images

Figure CN119592922A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermal insulation films, and in particular to a highly thermally insulating and environmentally friendly rare gold targeted thermal insulation film and a production method thereof. Background Art
[0002] With the development of science and technology, the improvement of people's living standards and the introduction of the concept of "low-carbon life", the performance requirements for thermal insulation films are getting higher and higher, and the demand is also gradually increasing. At present, thermal insulation films have been widely used in curtain wall glass of large buildings and window glass of cars. Using them on curtain wall glass of large buildings can greatly reduce air conditioning costs and make the appearance of the building have beautiful colors. At present, most car window glasses are affixed with thermal insulation films, which reduce the damage of ultraviolet rays to the human body and car interior decorations, slow down the aging of car facilities, reduce the temperature of the car environment, improve the riding environment of drivers and passengers, and also reduce the fuel consumption of cars and save car costs.
[0003] Glass insulation usually adopts the method of glass film. The comprehensive performance of thermal insulation film is excellent and it is widely used. However, the thermal insulation film needs to be attached to the glass with glue or other adhesives. When it is removed, it usually leaves any traces or residues. In addition, the glue or other adhesives contain volatile organic compounds, which may have adverse effects on human health and the environment, and do not conform to the environmental protection concept of modern home life. Summary of the invention
[0004] The present invention provides a highly heat-insulating and highly environmentally friendly rare-gold targeted heat-insulating film and a production method thereof, in order to solve the problems raised in the above-mentioned background technology.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A method for producing a highly heat-insulating and environmentally friendly rare-gold targeted heat-insulating film comprises the following preparation steps: Step S1, preparing a polyester film with a thickness of 2 mm; Step S2, mixing nano-lanthanum oxide powder with a star-shaped nanostructure, nano-yttrium oxide powder with a star-shaped nanostructure and copper powder in a ratio of 3-5:3-5:7 to obtain a mixed powder, heating the mixed powder to 2540-2600° C., and keeping the temperature for 1-2 hours to obtain a thermal insulation alloy; Step S3, magnetron sputtering is performed on both sides of the polyester film in step S1 to deposit a heat-insulating layer as a heat-insulating protection. The process conditions are: the heat-insulating alloy prepared in step S2 is used as the target material, the sputtering gas is 99.95% high-purity argon, and the vacuum degree inside the cavity is 4.5×10 -4Pa, the working pressure is set to 0.7Pa, the alloy target distance is fixed at 75mm, the argon flow rate is 22sccm, the sputtering power of the insulation alloy is 70W, the sputtering rate is 4.0nm / min, and the thickness of the insulation layer is 10nm.
[0006] As a further improvement of the technical solution: the preparation method of the star-shaped nanostructured lanthanum oxide powder is: The graphene-ethanol suspension is slowly added to the lanthanum salt solution, and the pH value of the solution is adjusted to 10. The mixed solution is then subjected to a solvothermal reaction at 190°C. After the reaction is completed, a vacuum freeze-drying technique is used to obtain a graphene / lanthanum precursor complex. Afterwards, the complex is placed in a magnetic boat and pushed to the center of a corundum reaction tube in a horizontal tube furnace. Air is introduced and the complex is heated to 750°C at a rate of 10°C per minute. After a heat treatment for 3 hours, the complex is naturally cooled to room temperature to obtain a nano-lanthanum oxide powder with a star-shaped nanostructure.
[0007] As a further improvement of the technical solution: the alkaline precipitant is one of ammonia water and sodium hydroxide.
[0008] As a further improvement of the technical solution: the preparation method of nano yttrium oxide powder with star-shaped nanostructure is: After mixing 0.35 mol / L yttrium chloride solution with 100 g / L polyethylene glycol solution, agricultural ammonium bicarbonate solution is then added dropwise to the mixed solution until yttrium ions are completely precipitated as yttrium carbonate to obtain an yttrium carbonate filter cake, and 20 g / L polyethylene glycol solution is added to the filter cake, and continuous strong stirring is performed to form yttrium carbonate precipitate foam. Subsequently, the foam sample is dried at 120° C., and then placed in a muffle furnace and heat treated at 470° C. for 2 hours, and then naturally cooled to room temperature to finally obtain a nano yttrium oxide powder with a star-shaped nanostructure.
[0009] As a further improvement of the present technical solution: the polyester film prepared in step S1 also needs to be washed with a detergent for 60 minutes in step S3 to remove organic solvents and dust impurities on the surface of the polyester film, and then repeatedly rinsed with deionized water and placed in an oven at 55-65°C for drying.
[0010] As a further improvement of the technical solution: in step S2, nano-lanthanum oxide powder with a star-shaped nanostructure, nano-yttrium oxide powder with a star-shaped nanostructure and copper powder are mixed in a ratio of 3:3:7 to obtain a mixed powder.
[0011] As a further improvement of the technical solution: in step S2, nano-lanthanum oxide powder having a star-shaped nanostructure, nano-yttrium oxide powder having a star-shaped nanostructure and copper powder are mixed in a ratio of 4:4:7 to obtain a mixed powder.
[0012] As a further improvement of the technical solution: in step S2, nano-lanthanum oxide powder having a star-shaped nanostructure, nano-yttrium oxide powder having a star-shaped nanostructure and copper powder are mixed in a ratio of 5:5:7 to obtain a mixed powder.
[0013] The present invention also provides a highly thermally insulating and environmentally friendly rare gold targeted thermal insulation film, which is manufactured using any of the above-mentioned methods for producing the highly thermally insulating and environmentally friendly rare gold targeted thermal insulation film.
[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. The heat-insulating film proposed by the present invention adopts the principle of electrostatic adsorption. The heat-insulating film does not need to use glue or other adhesives. It can be easily attached to the glass surface by electrostatic action. It is also very convenient to remove without leaving any traces or residues, thereby protecting the integrity of the glass surface. At the same time, since no harmful adhesives are needed, the pollution to the environment is reduced. It can be widely used in curtain wall glass and automobile window glass. 2. When sunlight passes through the thermal insulation film, the yttrium oxide and lanthanum oxide rare earth nanoparticles with star-shaped nanostructures in the thermal insulation film proposed by the present invention will produce a plasma resonance effect (LSPR effect), thereby absorbing a large amount of infrared and ultraviolet rays in the sunlight, producing the effect of isolating solar thermal radiation, and achieving the characteristic indicators of high infrared blocking rate and high thermal insulation.
[0015] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. The specific implementation of the present invention is given in detail by the following embodiments and their accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 A schematic diagram of the structure of a high-insulation, high-environmental-friendly rare-gold targeted thermal insulation film and a production method thereof proposed by the present invention; DETAILED DESCRIPTION
[0017] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention. The present invention is described in more detail by way of example with reference to the accompanying drawings in the following paragraphs. It should be noted that the accompanying drawings are all in a very simplified form and are not in precise proportions, and are only used to facilitate and clearly assist in explaining the purpose of the embodiments of the present invention.
[0018] Embodiment 1 A method for producing a highly heat-insulating and environmentally friendly rare-gold targeted heat-insulating film comprises the following preparation steps: Step S1, preparing a polyester film, the thickness of the polyester film is 2 mm, the polyester film (PET) is made of polyethylene terephthalate as a raw material, is made into a thick sheet by extrusion, and then is made into a film material by biaxial stretching, the polyester film is prepared by an existing conventional method, and its preparation is not described in detail, after preparation, the polyester film is washed with a detergent for 60 minutes to remove organic solvents, dust and impurities on the surface of the polyester film, and then it is repeatedly rinsed with deionized water and placed in an oven at 55-65°C for drying; Step S2, mixing nano-lanthanum oxide powder with a star-shaped nanostructure, nano-yttrium oxide powder with a star-shaped nanostructure and copper powder in a ratio of 3:3:7 to obtain a mixed powder, heating the mixed powder to 2540-2600° C., and keeping the temperature for 1-2 hours to obtain a thermal insulation alloy; Step S3, magnetron sputtering is performed on both sides of the polyester film in step S1 to deposit a heat-insulating layer as a heat-insulating protection. The process conditions are: the heat-insulating alloy prepared in step S2 is used as the target material, the sputtering gas is 99.95% high-purity argon, and the vacuum degree inside the cavity is 4.5×10 -4 Pa, the working pressure is set to 0.7Pa, the alloy target distance is fixed at 75mm, the argon flow rate is 22sccm, the sputtering power of the insulation alloy is 70W, the sputtering rate is 4.0nm / min, and the thickness of the insulation layer is 10nm, then a highly insulation and environmentally friendly rare gold targeted insulation film can be obtained.
[0019] The preparation method of the star-shaped nanostructured lanthanum oxide powder is as follows: Using ultrasonic technology, 24 mg of graphene was evenly dispersed in 175 ml of ethanol solution, and a stable graphene-ethanol suspension system was formed after 8 hours. At the same time, a lanthanum salt solution with a concentration of 0.8 mol / L was prepared. Subsequently, the above-mentioned graphene-ethanol suspension was slowly added to the lanthanum salt solution, and alkaline precipitants (including ammonia water and sodium hydroxide) were added in time to adjust the pH of the solution to 10 and mix evenly. Then, the mixed solution was transferred to a polytetrafluoroethylene reactor and subjected to a solvothermal reaction at 190°C for 10 hours. After the reaction, the solution was cooled and dried at -70°C for 45 hours using vacuum freeze drying technology, while maintaining a vacuum degree of 55 Pa, and finally a graphene / lanthanum precursor complex was obtained. After that, the complex was placed in a magnetic boat, pushed to the center of the corundum reaction tube of the horizontal tube furnace, air was introduced, and heated to 750°C at a rate of 10°C per minute for 3 hours of heat treatment. After the powder is cooled naturally to room temperature, nano-lanthanum oxide powder with a star-shaped nanostructure is obtained.
[0020] The preparation method of nano yttrium oxide powder with star-shaped nanostructure is as follows: Yttrium oxide is dissolved in hydrochloric acid and then diluted to ensure that the yttrium ion concentration reaches 0.35mol / L, and the pH value of the solution is adjusted to between 3-5. Next, the yttrium chloride solution is filtered using a double-layer quantitative filter paper. 40 liters of the filtered solution are placed in a 100-liter container, and 5 liters of 100g / L polyethylene glycol solution are added thereto, while the stirring rate is controlled at 300 revolutions per minute. Next, 100g / L agricultural ammonium bicarbonate solution is added dropwise to the solution at a rate of 0.5 liters per minute until the yttrium ions are completely precipitated as yttrium carbonate. After filtering and washing the obtained precipitate, 15 liters of 20g / L polyethylene glycol solution are added to the filter cake, and it is vigorously stirred for 5 hours while controlling the temperature to form a yttrium carbonate precipitate foam. Subsequently, the foam sample is dried at 120°C, placed in a muffle furnace, and heat treated at 470°C for 2 hours. After the powder is cooled naturally to room temperature, nano yttrium oxide powder with a star-shaped nanostructure is finally obtained.
[0021] Embodiment 2 The difference between the second embodiment and the first embodiment is that in step S2, the nano-lanthanum oxide powder having a star-shaped nanostructure, the nano-yttrium oxide powder having a star-shaped nanostructure and the copper powder are mixed in a ratio of 4:4:7 to obtain a mixed powder.
[0022] Embodiment 3 The difference between Example 3 and Example 1 is that in step S2: nano-lanthanum oxide powder with a star-shaped nanostructure, nano-yttrium oxide powder with a star-shaped nanostructure and copper powder are mixed in a ratio of 5:5:7 to obtain a mixed powder.
[0023] The infrared transmittance, light transmittance, temperature rise and adsorption force tests were performed on the above-mentioned Examples 1, 2 and 3. The test results are shown in Table 1 below. Infrared transmittance test method: First, the thermal insulation films prepared in Examples 1, 2, and 3 were placed in a UV-visible near-infrared spectrophotometer (UH4150 manufactured by Hitachi High-TechScience) and infrared rays of all wavelengths from 800 to 2500 nm were irradiated to the thermal insulation films. Then, the intensity of the infrared rays that passed through the thermal insulation films was divided by the intensity of the infrared rays that irradiated the test film to calculate the transmittance of each wavelength, and the average value of the transmittance was taken as the infrared transmittance.
[0024] Light transmittance test method: The heat-insulating films prepared in Examples 1, 2, and 3 were placed in a haze meter (NDH4000 manufactured by Nippon Denshoku Industries Co., Ltd.), and the total light transmittance was calculated according to JIS K7361; Temperature rise test method: prepare an internal space (volume 1000cm3 ), and a shell connected to the opening of the internal space. Then, the thermal insulation film prepared in Examples 1, 2, and 3 is attached to the surface to seal the opening. After the opening of the shell is sealed with the thermal insulation film, the temperature of the internal space is measured. This temperature is set as the pre-test temperature. Next, use an incandescent bulb (RF100V54WD manufactured by Panasonic Corporation) 60W type 200 lux to irradiate the thermal insulation film for 45 minutes. Then, measure the temperature of the internal space after the test. This temperature is taken as the post-test temperature. The difference between the post-test temperature and the pre-test temperature is set as the temperature rise.
[0025] Adsorption force test method: The thermal insulation films prepared in Examples 1, 2, and 3 were cut into a size of 200 mm × 220 mm, and then directly scraped and attached to a glass plate, and a label was attached in a manner that the 20 mm width portion at the lower end of the thermal insulation film protruded, and a clip was installed at the lower end of the label. 10 g weights tied with a line were added to the clip one by one, and the adsorption force converted to a unit square meter was calculated from the weight of the weight when the thermal insulation film fell; Table 1 Embodiment 1 Embodiment 2 Embodiment 3 Infrared transmittance 11% 8% 13% Light transmittance 75% 76% 76% Temperature rise 4℃ 3℃ 4℃ Adsorption 8600g / m2 8800g / m2 8700g / m2 As can be seen from the above table, the thermal insulation film prepared by the present invention has characteristic indicators such as high infrared blocking rate, high thermal insulation, and high adsorption force, and can meet high-requirement and high-index use fields. Among them, nano lanthanum oxide powder and nano yttrium oxide powder have special f orbital electron structures. When lanthanum oxide, yttrium oxide and copper powder are combined, these f orbital electrons can participate in the formation of chemical bonds and the transfer of charges when forming a thermal insulation alloy. Their f orbital electrons can contribute to the entire system and form a dense charge area. When the thermal insulation alloy is accurately applied to the thermal insulation film through targeted technology, a large amount of dense charges are generated on the surface of the thermal insulation film, so that the thermal insulation film can be firmly and durably attached to the glass surface by adopting the principle of electrostatic adsorption, and can be widely used in curtain wall glass and automobile window glass; In addition, both nano yttrium oxide powder and nano lanthanum oxide powder are star-shaped nanostructures, which have a central node and multiple nanorods extending from the node. These nanorods are arranged radially in space to form a star-like shape. This structure allows lanthanum oxide, yttrium oxide and copper powder to be combined. When sunlight passes through glass with added thermal insulation material, the yttrium oxide and lanthanum oxide rare earth nanoparticles in the thermal insulation layer will undergo a plasma resonance effect (LSPR effect), thereby absorbing a large amount of infrared and ultraviolet rays in the sunlight, resulting in the effect of isolating the sun's thermal radiation.
[0026] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as shown in the drawings and described above. However, any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
Claims
1. A method for producing a highly heat-insulating and environmentally friendly rare-gold targeted heat-insulating film, characterized in that: The method comprises the following preparation steps: Step S1, preparing a polyester film with a thickness of 2 mm; Step S2, mixing nano-lanthanum oxide powder with a star-shaped nanostructure, nano-yttrium oxide powder with a star-shaped nanostructure and copper powder in a ratio of 3-5:3-5:7 to obtain a mixed powder, heating the mixed powder to 2540-2600° C., and keeping the temperature for 1-2 hours to obtain a thermal insulation alloy; Step S3, magnetron sputtering is performed on both sides of the polyester film in step S1 to deposit a heat-insulating layer as a heat-insulating protection. The process conditions are: the heat-insulating alloy prepared in step S2 is used as the target material, the sputtering gas is 99.95% high-purity argon, and the vacuum degree inside the cavity is 4.5×10 -4 Pa, the working pressure is set to 0.7Pa, the alloy target distance is fixed at 75mm, the argon flow rate is 22sccm, the sputtering power of the insulation alloy is 70W, the sputtering rate is 4.0nm / min, and the thickness of the insulation layer is 10nm.
2. The method for producing a highly heat-insulating and environmentally friendly rare-gold targeted heat-insulating film according to claim 1, characterized in that: The preparation method of the star-shaped nanostructured lanthanum oxide powder is as follows: The graphene-ethanol suspension is slowly added to the lanthanum salt solution, and then an alkaline precipitant is added dropwise to adjust the pH value of the solution to 10. The mixed solution is then subjected to a solvothermal reaction at 190°C. After the reaction is completed, a vacuum freeze-drying technique is used to obtain a graphene / lanthanum precursor complex. Afterwards, the complex is placed in a magnetic boat and pushed to the center of a corundum reaction tube in a horizontal tube furnace. Air is introduced and the complex is heated to 750°C at a rate of 10°C per minute. After a heat treatment for 3 hours, the complex is naturally cooled to room temperature to obtain a nano-lanthanum oxide powder with a star-shaped nanostructure.
3. The method for producing a highly heat-insulating and environmentally friendly rare-gold targeted heat-insulating film according to claim 2, characterized in that: The alkaline precipitant is one of ammonia water and sodium hydroxide.
4. The method for producing a highly heat-insulating and environmentally friendly rare-gold targeted heat-insulating film according to claim 1, characterized in that: The preparation method of nano yttrium oxide powder with star-shaped nanostructure is as follows: After mixing 0.35 mol / L yttrium chloride solution with 100 g / L polyethylene glycol solution, agricultural ammonium bicarbonate solution is then added dropwise to the mixed solution until yttrium ions are completely precipitated as yttrium carbonate to obtain an yttrium carbonate filter cake, and 20 g / L polyethylene glycol solution is added to the filter cake, and continuous strong stirring is performed to form yttrium carbonate precipitate foam. Subsequently, the foam sample is dried at 120° C., and then placed in a muffle furnace and heat treated at 470° C. for 2 hours, and then naturally cooled to room temperature to finally obtain a nano yttrium oxide powder with a star-shaped nanostructure.
5. The method for producing a highly heat-insulating and environmentally friendly rare-gold targeted heat-insulating film according to claim 1, characterized in that: The polyester film prepared in step S1 also needs to be washed with a detergent for 60 minutes in step S3 to remove organic solvents, dust and impurities on the surface of the polyester film, and then repeatedly rinsed with deionized water and placed in an oven at 55-65° C. for drying.
6. The method for producing a highly heat-insulating and environmentally friendly rare-gold targeted heat-insulating film according to claim 1, characterized in that: In step S2, nano-lanthanum oxide powder having a star-shaped nanostructure, nano-yttrium oxide powder having a star-shaped nanostructure and copper powder are mixed in a ratio of 3:3:7 to obtain a mixed powder.
7. The method for producing a highly heat-insulating and environmentally friendly rare-gold targeted heat-insulating film according to claim 1, characterized in that: In step S2, nano-lanthanum oxide powder having a star-shaped nanostructure, nano-yttrium oxide powder having a star-shaped nanostructure and copper powder are mixed in a ratio of 4:4:7 to obtain a mixed powder.
8. The method for producing a highly heat-insulating and environmentally friendly rare-gold targeted heat-insulating film according to claim 1, characterized in that: In step S2, nano-lanthanum oxide powder having a star-shaped nanostructure, nano-yttrium oxide powder having a star-shaped nanostructure and copper powder are mixed in a ratio of 5:5:7 to obtain a mixed powder.
9. A highly heat-insulating and environmentally friendly rare-gold targeted heat-insulating film, characterized in that: The highly heat-insulating and environmentally friendly rare gold targeted heat-insulating film is manufactured by the production method described in any one of claims 1 to 8.